The evolution of antimicrobial resistance in Salmonella Typhi - Karkey, A; Thwaites, G; Baker, S (Lippincott, Williams & Wilkins, 2017)
Increasing antimicrobial resistance in Salmonella Typhi is a serious public health concern, especially in industrializing countries. Here we review recent clinical and laboratory data concerning the evolution of antimicrobial resistance, with particular reference to the emergence resistance against fluoroquinolones, third generation cephalosporins, and azithromycin.The last 40 years have witnessed the sequential emergence of resistance to all first-line antimicrobials used in the treatment of S. Typhi infections. Multidrug resistance (MDR), defined by resistance to chloramphenicol, amoxicillin, and co-trimoxazole, emerged in the 1990s, followed rapidly by reduced susceptibility to fluoroquinolones. In the current decade, high-level fluoroquinolone resistance has emerged in south Asia and threatens to spread worldwide. Increasing reliance is now being placed on the activity of third generation cephalosporins and azithromycin, but resistance against these agents is developing. Carbapenems and tigecycline may be alternatives, although clinical data are sparse, and in some settings reversion to chloramphenicol and co-trimoxazole susceptibility is occurring. Therefore, older drugs may yet have a role in the treatment of S. Typhi infections.Good surveillance, improved diagnostics, more prudent use of antimicrobials, and effective vaccines will all be critical to reducing the burden of disease caused by S. Typhi.